N-Acetyl cysteine and erdosteine treatment in acetaminophen-induced liver damage. (August 2014) - Saritas, Ayhan; Kandis, Hayati; Baltaci, Davut; Yildirim, Umran; Kaya, Halil; Karakus, Ali; Colakoglu, Serdar; Memisogullari, Ramazan; Kara, Ismail Hamdi
Objective: This study is aimed to investigate the efficacy of erdosteine usage in acetaminophen-induced liver damage and to compare it with N -acetyl cysteine (NAC) in the treatment and prevention of liver toxicity due to overdose of acetaminophen. Methods: The rats were separated into the following six groups of seven rats each: control group; acetaminophen (1 g/kg, orally); acetaminophen (1 g/kg, orally) + erdosteine (150 mg/kg/day, orally); acetaminophen (1 g/kg, orally) + NAC (140 mg/kg loading dose, followed by 70 mg/kg, orally); NAC (140 mg/kg loading dose, followed by 70 mg/kg, orally); erdosteine (150 mg/kg/kg, orally), subsequently. In all the groups, potential liver injuries were evaluated using biochemical and hematological analyses, oxidant–antioxidant parameters and histopathological parameters. Results: In acetaminophen-treated group, levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total oxidant status (TOS) in the blood, prothrombin time (PT) and international normalized ratio (INR) were significantly increased when compared with controls. However, total antioxidant capacity (TAC) and glutathione (GSH) levels were decreased in group treated with acetaminophen, when compared with control group. Levels of AST, ALT and TOS, PT and INR were decreased in groups treated with NAC and erdosteine after acetaminophen administration, but the levels of TAC and GSH were increased. Histopathological improvements were observed in the groups treated with NAC and erdosteine after acetaminophen administration. Conclusion: The present study demonstrated that, in the prevention of liver damage induced by acetaminophen intoxication, an early treatment with a single dose of erdosteine was beneficial instead of NAC administration.